Penerapan Konseling Kelompok Rational Emotive Behavior dan Psikoedukasi di Sekolah Islam; Dampaknya terhadap Penalaran Moral Siswa - Purwati Purwati; Muhammad Japar; Laili Qomariyah (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
Along with the development of the times and culture's contact from outside, the moral boundaries that are firmly held by the community are increasingly unclear. At school, for example, many students experience a decline in moral reasoning. However, the limited literature that focuses on improving moral reasoning with a quasi-experimental approach, the author will examine psychological interventions Rational Emotive Behavior Counseling (REB) and Psychoeducation (PSE). This study aims to identify differences in effectiveness between group counseling interventions with PSE and REB in improving students' moral reasoning. The author uses a quasi-experiment with a pretest-posttest follow-up design. The study subjects were Sarbini Islamic Junior High School students who had low moral levels. The research subjects consisted of 22 students divided into 11 students in the PSE group and 11 students in the counseling group with the REB approach. The data analysis results showed differences in students' moral reasoning in the REB and PSE groups. The average increase in students' moral reasoning was higher in the REB group than in the PSE group. The author concludes that group counseling with REB and PSE approaches can be applied to improve moral reasoning in students in schools, especially those based on Islam. However, for more optimal results, the authors suggest using REB.